The application of information and communication technology in education : science classes - Merjem Rustempašić, Sanela (Array, 2021)
This article examines the use of information and communication technology (ICT) in teaching Science as well as the organisation and realisation of online classes during the ongoing COVID-19 pandemic. In respect to this, the research results are used to gather teachers' viewpoints and opinions regarding the application of ICT in Science classes, as well as to determine the best method of application of the aforementioned technologies and the form of ICT most often used in Science classes. The results are also used to gather teachers' opinions about online classes, and to examine the problems and disadvantages the teachers encountered when organising and holding online Science classes for the lower grades of elementary schools in Bosnia and Herzegovina during the COVID-19 pandemic. The results of the research also illustrate that teachers have a positive opinion in regards to the use of ICT in Science classes as well as the frequent (albeit not constant) use of it. The teachers not only consider themselves competent enough to apply all forms of new technologies in their classes, but express the will and motivation for further education related to ICT application as well. On the other hand, teachers do not have a positive opinion about online classes due to the many difficulties they encounter, such as technical issues, inteference by parents, lack of direct contact with students, the inability to monitor their progress and the general deficiency of equipment needed to incorporate ICT into regular classes, as well as other difficulties of a similar nature. However, the research results also show that teachers believe new technologies are connected to the development of new skills and the improvement of students' existing skills.